2000
DOI: 10.4049/jimmunol.164.1.371
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 and IL-10 Antagonize IL-12-Mediated Protection Against Acute Vaccinia Virus Infection with a Limited Role of IFN-γ and Nitric Oxide Synthetase 2

Abstract: Resistance or susceptibility to most infectious diseases is strongly determined by the balance of type 1 vs type 2 cytokines produced during infection. However, for viruses, this scheme may be applicable only to infections with some cytopathic viruses, where IFN-γ is considered as mandatory for host defense with little if any participation of type 2 responses. We studied the role of signature Th1 (IL-12, IFN-γ) and Th2 (IL-4, IL-10) cytokines for immune responses against vaccinia virus (VV). IL-12−/− mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
2
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 90 publications
7
91
2
1
Order By: Relevance
“…More importantly, blocking IL-10 signaling did not abrogate or impair VACV replication in the ovaries and the other visceral organs, and did not positively affect the generation of antibodies against VACV. The reasons for the discrepancy noted between our data and those of another publication (23), that claimed that IL-10 -/ -mice had reduced replication of VACV in the ovaries, is not clear. The onset and severity of both spontaneous and experimentally-induced inflammation in IL-10 -/ -mice may be strongly influenced by the conditions in which these mice are kept.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…More importantly, blocking IL-10 signaling did not abrogate or impair VACV replication in the ovaries and the other visceral organs, and did not positively affect the generation of antibodies against VACV. The reasons for the discrepancy noted between our data and those of another publication (23), that claimed that IL-10 -/ -mice had reduced replication of VACV in the ovaries, is not clear. The onset and severity of both spontaneous and experimentally-induced inflammation in IL-10 -/ -mice may be strongly influenced by the conditions in which these mice are kept.…”
Section: Discussioncontrasting
confidence: 56%
“…4f ). However, this is in contrast with the 10,000-fold reduction reported in the prior report (23). Virus titers were not significantly different in IL-10 -/ -mice in the ovaries at day 15 post-infection (Fig.…”
Section: Il-10 and Tgf-b Do Not Control Vacv Replicationcontrasting
confidence: 56%
“…Several groups have reported that insertion of Th2 -like cytokines such as IL -4 or IL -10 into vaccinia virus increases in vivo viral replication and slows host clearance of infection. 25,48 However, creation of a virus that is not recognized by the immune system obviously creates serious safety concerns for the population as a whole, as unforeseen events could …”
Section: Improving In Vivo Replication Efficacy Of Vaccinia Virus By mentioning
confidence: 99%
“…Van Den et al 25 examined the effect of Th1 (IFN -g, IL -12 ) and Th2 ( IL-4, IL -10 ) balance in the clearance of vaccinia virus in mice using cytokine knockouts. Vaccinia viral replication was enhanced in IL -12 and IFN -g knockout mice, with IL -12( À / À ) demonstrating greater susceptibility to infection than IFN -g -deficient mice.…”
Section: Vaccinia Virus Biologymentioning
confidence: 99%
“…IL-4 and IL-10 promote VV spread (4,5). In contrast, IFN-␥ (6), IgG antibody (7), CD8 ϩ cytotoxic T cells (8), NK cells (9), and the cathelicidin family of antimicrobial peptides (AMPs) (10) are thought to contribute to VV containment.…”
mentioning
confidence: 99%